'Stops walking to talk': a simple measure of predicting falls in the frail elderly - Nitz, Jennifer C.; Thompson, Karen J. (Australasian journal on ageing, 2003)
Objective: To discover if the measure ‘stops walking to talk’ is a useful indicator of falls risk in the frail elderly in residential care. Method: Twelve frail elderly residents of care facilities were assessed for falls likelihood with the Timed Up‐and‐Go (TUG) and the Berg Balance Scale (BBS) tests, and then observed in walking to determine if they needed to stop walking to talk. These results were compared with the number of falls subjects had experienced in the previous six months. Results: Eight subjects were deemed at risk of falling by the TUG and seven by the BBS. Four of these subjects had fallen in the previous six months. Three subjects needed to stop walking to talk on at least one occasion and were deemed at risk of falling by the TUG and BBS. One of these had fallen in the previous six months. Conclusion: This study demonstrated in this group of frail older people that falling in the previous six months was associated with high TUG and low scores on the BBS. Only three observations of ‘stops walking to talk’ were made; this limited the comparisons as only one of these subjects had fallen but all were predicted as falters by the TUG and BBS. A future study with a larger sample size and incorporating memory recall in the conversation should confirm these results.